Interpersonal Communication And Patient Satisfaction With Midwifery Services - Astin Nur Hanifah; Imelda Kardina; Rika Rika; Azmi Wijayanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Interpersonal communication is a crucial factor in determining the quality of the midwife-patient relationship. Effective communication in midwifery services can enhance patient comfort, trust, and satisfaction. This study aimed to determine the relationship between midwives' interpersonal communication and patient satisfaction with midwifery services at Community Health Center X. This type of research is quantitative with a cross-sectional design. Sectional. The population in this study were all patients who received obstetric services at Community Health Center X during May–July 2025, totaling 80 people. The sample was taken using an accidental sampling technique of 67 respondents. The instruments used were a midwife interpersonal communication questionnaire (15 items) and a patient satisfaction questionnaire (15 items) that had been tested for validity and reliability. Data were analyzed using the Chi- Square statistical test with a significance level of 0.05. The results showed that the majority of respondents rated midwives' interpersonal communication as good (71.6%) and patient satisfaction as satisfactory (68.7%). The Chi- Square test yielded a p-value of 0.002 (<0.05), indicating a significant relationship between midwives' interpersonal communication and patient satisfaction with midwifery services. In conclusion, the better the interpersonal communication skills developed by midwives, the higher the patient satisfaction levels. Therefore, improving midwives' interpersonal communication skills through training and coaching should be a priority in efforts to improve the quality of midwifery services.